Feed and wrap magnetic resonance urography provides anatomic and functional imaging in infants without anesthesia. Issue 1 (February 2020) - Kurugol, Sila; Seager, Catherine M.; Thaker, Hatim; Coll-Font, Jaume; Afacan, Onur; Nichols, Reid C.; Warfield, Simon K.; Lee, Richard S.; Chow, Jeanne S.
Summary: Objective: To describe a technique for performing magnetic resonance urogram (MRU) in infants without sedation or anesthesia. Methods: Eighteen infants underwent MRU in the absence of sedating medications using a 'feed and wrap' technique (FW-MRU). Dynamic contrast enhanced images were obtained. Dynamic radial VIBE and compressed sensing image reconstruction were used to correct for motion artifact. Results: Seventeen of the 18 patients had successful FW-MRU. Feed and wrap' magnetic resonance urogram provided high-quality anatomic and functional renal data. Conclusion: Initial experience with FW-MRU demonstrates it to be a promising anesthesia-free modality for obtaining anatomic and functional imaging of the urinary tract in infants.